Unveiling the Social Media Magic How TAM, TPB, and Trust Shape Behavior Intentions in the Tourism Sector - Khan, Safdar; Adil, Mohd; Rehman, Asad (Politeknik Negeri Bandung, 2025)
Currently, social media plays a pivotal role in the tourism industry, shaping travelers' intentions. In this research, a comprehensive context that combines the TAM proposed by Davis (1989), TPB introduced by Ajzen (1991), and trust is utilized to investigate Social Media Impact on Behavior Intention in the Tourism Sector. In this research, a convenience sampling approach was employed. The data was gathered using an online questionnaire shared via social network pages between October 10, 2023, to November 20, 2023. Hypothesis testing was carried out using the PLS-SEM method, utilizing SmartPLS 3.0 as the statistical analysis software. The study's results showcase the success of merging the theory of planned behavior, technology acceptance model, and trust into a sturdy framework. This model effectively reveals social media impacts behavioral intentions in the tourism industry. Importantly, all hypotheses were confirmed, underscoring the framework's importance in understanding consumer behavior regarding social media and its impact on travel choices. This research delves into how social media affects travel destination choices for Indian consumers. It provides valuable insights into the behavioral intentions of key players in the travel industry, including online tourism businesses, tour managers, and organizers. This study is limited to the Indian context. It offers a distinct contribution by conducting a thorough analysis of the existing research panorama concerning Unveiling the social media Magic: How TAM, TPB, and Trust Shape Behavior Intentions in the Tourism Sector.